Desain Pengembangan Kurikulum di Pondok Pesantren Salafiyyah Hidayatul Mubtadi’ien Kota Bengkulu - Desy Eka Citra Dewi; Muhammad Agus Ainur Rasyid (UIN Fatmawati Sukarno Bengkulu, 2025)
This research discusses the curriculum development design of Salafiyyah Hidayatul Mubtadi'ien Islamic Boarding School in Bengkulu city. The research aims to find out how the curriculum development design at Hidayatul Mubtadi'ien Salafiyyah Islamic Boarding School in Bengkulu city. This research was conducted using a qualitative method, which is a method directed at the setting and individuals holistically (whole). The population in this study was the Hidayatul Mubtadi'ien salafiyyah boarding school in Bengkulu city. The results showed that factually, the Hidayatul Mubtadi'ien salafiyah boarding school in Bengkulu city is an Islamic educational institution that still maintains its traditionalism both in terms of curriculum and learning system. This is revealed that the curriculum that is applied only emphasizes the learning of classical books (yellow books) by exploring and examining the sciences contained therein. This means that the main focus of Hidayatul Mubtadi'ien Salafiyah Islamic Boarding School in Bengkulu city is not teaching general knowledge. Explicitly, the curriculum of Pondok Pesantren Salafiyah Hidayatul Mubtadi'ien Bengkulu city consists of intracurricular, co-curricular and extracurricular curricula.